Literasi Media Digital Mahasiswa Universitas Jenderal Soedirman - Dyah Perwita (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
This study aims to determine the understanding of digital media literacy of student at Jenderal Soedirman University. This research was using a qualitative research approach and descriptive survey methods with descriptive statistical data analysis techniques. Data collection techniques using the method of observation, questionnaires, and documentation. This research was focus on active students enrolled in the even semester of the 2019 ~ 2020 academic year. Students who have and actively use gadgets are the respondents who are focused in this study. The number of students who became research respondents was 660 students. Individual Competence has two parts of the study, namely personal competence and social competence. The individual level of competence are technical skills, critical understanding, and social competence. The results of this study indicate that the understanding of Jenderal Soedirman University students regarding digital media literacy is quite high. This can be seen from: 1. As many as 94.4 percent are in the advanced category of mastery of digital media use; 2. As many as 80.6 percent are in the advanced category of ability to give criticism in the media; 3.As many as 70.8 percent are in the medium category with the ability to communicate through the media.